ESG and Financial Distress in Indonesian Non-Financial Firms: The Moderating Role of Cost of Debt - Muhammad Onto Kusumo; Gatot Nazir Ahmad; Umi Widyastuti (International Journal of Economics and Management Sciences, 2025)
This study examines how Environmental, Social, and Governance (ESG) performance influences financial distress, incorporating cost of debt as a moderating variable. Financial distress is proxied by the Interest Coverage Ratio (ICR), reflecting a firm’s capacity to satisfy interest payments. The empirical sample consists of 655 firm-year observations of non-financial companies listed on the Indonesia Stock Exchange from 2014 to 2023. Panel regression with fixed effects and heteroskedasticity-consistent estimation (Panel EGLS with cross-section weights) is employed to analyze the data. Results indicate that ESG performance exerts a positive and statistically significant effect on ICR (β = 0.1189; p < 0.01), implying that firms with robust ESG practices are better able to service their debt and thus face lower financial distress. Additionally, the interaction term between ESG and cost of debt yields a negative and significant coefficient (β = −0.9714; p < 0.05), suggesting that elevated financing costs attenuate the beneficial impact of ESG on financial resilience. These findings are consistent with stakeholder theory, which advocates that proactive engagement with stakeholders enhances corporate stability, and trade-off theory, which underscores the necessity of balancing debt advantages against financial risk. This research contributes to the literature by demonstrating the conditional effect of cost of debt on the ESG–financial distress nexus. From a managerial perspective, the study underscores the importance of integrating ESG initiatives with cost-efficient funding strategies to mitigate financial distress risk and foster sustainable, long-term value creation.